If it's not what You are looking for type in the equation solver your own equation and let us solve it.
=2(S+3)+4S-5
We move all terms to the left:
-(2(S+3)+4S-5)=0
We calculate terms in parentheses: -(2(S+3)+4S-5), so:We get rid of parentheses
2(S+3)+4S-5
We add all the numbers together, and all the variables
4S+2(S+3)-5
We multiply parentheses
4S+2S+6-5
We add all the numbers together, and all the variables
6S+1
Back to the equation:
-(6S+1)
-6S-1=0
We move all terms containing S to the left, all other terms to the right
-6S=1
S=1/-6
S=-1/6
| x2-6.5x+42=0 | | 1/2x^2+2x-1=0 | | -5x-7=-3x-17 | | 2/7a=-6 | | 9x-74=70 | | 2x-7-3x=6(x-1) | | 4-2(3x-7)=2(2x-9) | | 41-q=3(q+5) | | 7x-6-8x=-5x-6 | | 1/5(3x+3)=9 | | 3a^2-26a-40=0 | | 10x—20=13 | | (x+7)^2-11=0 | | 1/2y+5=1/7y | | 15/1=30/x | | (6x-1)+(5x+16)=125 | | 10x-10/5=(-18) | | 2x^2+2x=5x+9 | | 5x+4(x-5)=580 | | 8r+9=0 | | (1/2)y+5=(1/7)y | | f+(2f+2.50)=11.25 | | 10x-10/5=-18 | | 2/3=-x | | 8r-55=0 | | (3x+4)+(2x)+(3x)=180 | | 9x=288-7x | | 9^5x=23 | | 5(x-2)=4x-10 | | F(-5)=-12x+7 | | 5/4x=3/4x+10 | | 1x+4x=6+5x |